2013
DOI: 10.1515/ijamh-2013-0308
|View full text |Cite
|
Sign up to set email alerts
|

Iranian university students’ perceived reproductive health needs

Abstract: Taken as a whole, these findings support the critical importance of programming for university students as part of a comprehensive strategy to improve the health and development of young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Thus training communication skills is of the most important methods playing role in marriage relationship firmness and survival and in contrast, the most common issue set forth by dissatisfied couples is failure in communication. In this regard, the study performed among Iranian students implies that the highest demand for reproductive health training from the participants' perspective is the requirement of training the suitable behavior with the would-be spouse (52). So that in training programs, it seems this group of individuals has to be included appropriately from school to university level.…”
Section: Discussionmentioning
confidence: 99%
“…Thus training communication skills is of the most important methods playing role in marriage relationship firmness and survival and in contrast, the most common issue set forth by dissatisfied couples is failure in communication. In this regard, the study performed among Iranian students implies that the highest demand for reproductive health training from the participants' perspective is the requirement of training the suitable behavior with the would-be spouse (52). So that in training programs, it seems this group of individuals has to be included appropriately from school to university level.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the most common problem raised by dissatis ed couples is failure to relate. In this regard, the study among Iranian students shows that the highest need of reproductive health education from the participants' point of view is the need to train appropriate behavior with future spouse [23], which seems to be considered appropriate in the curriculum of this group of people from school to university.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of studies conducted in the Islamic Republic of Iran revealed that many of the tools used to define SRH needs were specific to particular groups-such as pre-marriage couples (10), students (11,12), people living with HIV/AIDS (12) and adolescents (13)-and there were no general SRH needs assessment tools that had been validated in the Iranian context. We therefore decided to adapt and test an international standard questionnaire for assessing women's SRH needs in a northern area of the Islamic Republic of Iran.…”
Section: Introductionmentioning
confidence: 99%